Ultrathin Ni(ii)-based coordination polymer nanosheets as a co-catalyst for promoting photocatalytic H2-production. Issue 46 (15th May 2019) - Jiang, Zhi-Qiang; Chen, Xing-Liang; Lu, Jin; Li, Yu-Feng; Wen, Tian; Zhang, Lei
Abstract : The Ni(ii ) coordination polymer nanosheets were successfully exfoliated, which can be used as co-catalysts (Ni-CPNS@CdS). The optimized Ni-CPNS@CdS catalyst showed a super high visible-light photocatalytic hydrogen production activity. Abstract : Ni(ii ) coordination polymer nanosheets (Ni-CPNS) were prepared via a top-down liquid ultrasonication exfoliation method. For the first time, Ni-CPNS was used as a co-catalyst (Ni-CPNS@CdS) via a mechanical grinding strategy. The optimized Ni-CPNS@CdS catalyst reached a super high visible-light photocatalytic hydrogen production activity of 10 210 μmol h −1 g −1, exceeding that of bare CdS nanoparticles by 1480%. Our work can open new avenues towards the design of stable and cheap CPNS co-catalysts to replace expensive and rare noble metals for photocatalysis processes.